A Study on the Implementation of Early Childhood Education Quality Assurance in Luang Prabang Province - Linthavong, Syphachanh; Vathanavong, Thongthiane; Thipphaphone, Kinnaly; Phanthong, Bounlai (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Early childhood education quality is important for human background development, this research aimed to Study on the Establishment and Implementation of Quality Assurance for Early Childhood Education in Luang Prabang Province. and Guidelines for Quality Assurance in Early Childhood Education in Luang Prabang. A total of 234 participants were involved in the study, including 102 school administrators, 99 teachers, and 33 members of village education development committees. Descriptive statistics, including mean and standard deviation, were employed for data analysis. The results of the research found that overall it was at a high level with a mean value of (4.03; S.D= 0.50). Based on the Context dimension, schools should ensure a safe and secure learning environment by providing strong fencing, functional handwashing facilities, and at least three types of outdoor play equipment. Regarding Input factors, teachers should be adequately equipped with child development monitoring records corresponding to the number of students, and schools should allocate teachers and students according to the prescribed teacher studentratio. In terms of the Process dimension, classrooms should be organized with at least three learning corners aligned with instructional units, and schools should conduct annual self-evaluations to identify unmet indicators and use the results for systematic school development planning. School administrators are encouraged to strengthen collaboration with parents, community organizations, and village education development committees to promote shared responsibility and community participation in school improvement and safety. For the Product dimension, teachers should employ diverse teaching approaches to enhance student motivation and engagement, while schools should recognize high-performing teachers and support their professional development in subject knowledge and educational technology.